PD-1 monoclonal antibodies as an effective treatment for rare cutaneous malignancies: a case report - Falk, Ryan; Samlowski, Wolfram; Hedayat, Amin (Frontiers in Oncology, 2025)
Adnexal carcinoma and adenosquamous carcinoma are rare forms of skin malignancy that are usually treated via surgical resection or radiotherapy. These cancers become clinically challenging when localized treatment is not feasible. In addition, the cosmetic and functional defects resulting from radical surgical resection of tumors in peri-orbital areas need to be considered. The checkpoint inhibitors pembrolizumab and cemiplimab have been effective treatments for a number of cutaneous malignancies. We present cases of adenosquamous skin cancer and eyelid sebaceous gland cancer that achieved rapid, complete pathological and radiological remission in response to treatment with single agent PD-1 monoclonal antibodies. These patients had minimal, if any toxicity associated with treatment and have each remained recurrence-free for over a year of follow up. The therapeutic potential of PD-1 monoclonal antibodies as a treatment for these rare skin malignancies warrants further evaluation in clinical trials.